Strategi Standarisasi dan Sertifikasi Produk Kuliner Berbahan Dasar Beras di Desa Wisata Sidan - Arisandhi, I Made Dimas; Dwi Susanti, Ida Ayu Made; Budiasa, I Made; Listihani, Listihani (Jurnal MeA (Media Agribisnis), 2024)
Organic farming is a holistic production management system that improves and develops the health of agroecosystems, including biodiversity, biological cycles and soil biological activity. Organic farming is increasingly being applied to several agricultural commodities, one of which is rice as a rice producing commodity. Mentik Susu organic rice products have become the mainstay product of Sidan Tourism Village. Mentik Susu organic rice can be processed and then developed into the main ingredient for traditional food typical of the Sidan Tourism Village. The aim of this research is to design a strategy based on program needs using the ISM method in the Sidan Tourism Village. Through ISM analysis, a standardization and certification strategy for rice-based culinary products in the Sidan Tourism Village was obtained.